YAP activation in Müller cells protects against NMDA-induced retinal ganglion cell injury by regulating Bcl-xL expression - Kashihara, Toshihide; Morita, Yui; Hatta, Misaki; Inoue, Sae; Suzuki, Yume; Morita, Akane; Nakahara, Tsutomu (Frontiers in Pharmacology, 2024)
Retinal neurodegeneration, characterized by retinal ganglion cell (RGC) death, is a leading cause of vision impairment and loss in blind diseases, such as glaucoma. Müller cells play crucial roles in maintaining retinal homeostasis. Thus, dysfunction of Müller cells has been implicated as one of the causes of retinal diseases. Yes-associated protein 1 (YAP), a nuclear effector of the Hippo pathway, regulates mammalian cell survival. In this study, we investigated the role of YAP in Müller cells during N-methyl-D-aspartic acid (NMDA)-induced excitotoxic RGC injury in rats. We found that YAP expression increased and was activated in Müller cells after NMDA-induced RGC injury. This YAP response was partly due to an increase in Yap mRNA levels, although it may be independent of the Hippo pathway and β-TrCP-mediated YAP degradation. Morphological analysis revealed that verteporfin, a selective YAP inhibitor, exacerbated NMDA-induced RGC degeneration, suggesting that YAP activation in Müller cells contributes to RGC survival in NMDA-treated retinas. Studies in the rat Müller cell line (rMC-1) demonstrated that overexpression of YAP increased the levels of Bcl-xL, while verteporfin decreased the levels of Bcl-xL and cell viability and increased the levels of cytochrome c released from mitochondria and cleaved caspase-3. Finally, we found that Bcl-xL expression increased slightly in NMDA-treated retinas, whereas intravitreal injection of verteporfin suppressed this increase. Our findings suggest that activated YAP in Müller cells protects against NMDA-induced RGC injury by upregulating Bcl-xL expression.